Scentralizowana baza danych dendrochronologicznych - Olichwirowicz, Marcin (My University, 2010)
The main goal was to create MySQL database, which gathers data about dendrochronological samples. As a support to this database, internet application Dendrobase was created. This allowed to modify, import and export information connected with samples and measurement data. In additional, this application is integrated with Trimean program by a proxy application which sends data to the database based on *.prd format files. The creation of Dendrobase simplify comparing and faster receiving measurement data which will be available in intranet. Information about samples will be stored in one, easily accessible place where they could be efficiently archive.

Głównym celem pracy było stworzenie centralnej bazy danych MySQL mającej za zadanie przechowywanie informacji o próbach dendrochronologicznych. Do jej obsługi stworzono aplikację internetową Dendrobase pozwalającą na modyfikację, importowanie oraz eksportowanie informacji dotyczących prób i danych pomiarowych. Dodatkowo aplikacja zintegrowana jest z programem Trimean za pomocą pośredniczącej aplikacji wysyłającej dane do bazy na podstawie dostarczanych plików w formacie *.prd. Dzięki DendroBase praca z danami pomiarowymi będzie szybsza, a jej efekty będą dostępne w intranecie. Informacje dotyczące prób będą przechowywane w jednym, łatwo dostępnym miejscu, gdzie mogą być skutecznie archiwizowane.
Centralised denrochronological database
Keywords: MySQL; próby dendrochronologiczne; aplikacja internetowa Dendrobase; MySQL; dendrochronological samples; internet application Dendrobase